A digital pathway for genetic testing in UK NHS patients with cancer: BRCA-DIRECT randomised study internal pilot. Issue 12 (22nd July 2022) - Torr, Bethany; Jones, Christopher; Choi, Subin; Allen, Sophie; Kavanaugh, Grace; Hamill, Monica; Garrett, Alice; MacMahon, Suzanne; Loong, Lucy; Reay, Alistair; Yuan, Lina; Valganon Petrizan, Mikel; et al.
Abstract : Background: Germline genetic testing affords multiple opportunities for women with breast cancer, however, current UK NHS models for delivery of germline genetic testing are clinician-intensive and only a minority of breast cancer cases access testing. Methods: We designed a rapid, digital pathway, supported by a genetics specialist hotline, for delivery of germline testing of BRCA1/BRCA2/PALB2 (BRCA-testing), integrated into routine UK NHS breast cancer care. We piloted the pathway, as part of the larger BRCA-DIRECT study, in 130 unselected patients with breast cancer and gathered preliminary data from a randomised comparison of delivery of pretest information digitally (fully digital pathway) or via telephone consultation with a genetics professional (partially digital pathway). Results: Uptake of genetic testing was 98.4%, with good satisfaction reported for both the fully and partially digital pathways. Similar outcomes were observed in both arms regarding patient knowledge score and anxiety, with <5% of patients contacting the genetics specialist hotline. All progression criteria established for continuation of the study were met. Conclusion: Pilot data indicate preliminary demonstration of feasibility and acceptability of a fully digital pathway for BRCA-testing and support proceeding to a full powered study for evaluation of non-inferiority of the fully digital pathway, detailed quantitative assessment of outcomes and operational economic analyses. Trial registration number: ISRCTN87845055 .